PERLINDUNGAN HUKUM HAK ATAS KEKAYAAN INTELEKTUAL TERHADAP PENGETAHUAN TRADISIONAL DI INDONESIA - Indra Putra, Ngurah Bagus; Suarbha, I Wayan (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 04, Juni 2013, 2013)
This paper shall be entitled as “Legal Protection of Intellectual Property Rights for Traditional Knowledge in Indonesia”. Research conducted on this paper shall be normative research on traditional knowledge, excluding the protection of Intellectual Property Right, itobviously damage endanger traditional societies. In response, the urgency of the protection of traditional knowledge protection shall no longer be limited to wait for an international consensus level, but there should be certain regulation of national protection. Added to that the goverment must react quickly in order to establish legal protection towards traditional knowledge in Indonesia.
Keywords: Intellectual Property Rights, Legal Protection, Traditional Knowledge